2011
DOI: 10.4278/ajhp.090826-quan-278
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Behaviors of Afghanistan and Iraq War Veterans Attending College

Abstract: Purpose The population military veterans attending college is rapidly growing as veterans return from Operations Enduring Freedom and Iraqi Freedom (OEF/OIF). We sought to describe patterns of student veterans’ health-related behaviors and how they might differ from their non-veteran peers. Design We analyzed data from the 2008 Boynton College Student Health Survey (CSHS). Setting CSHS participants completed an anonymous online survey. Subjects The CSHS sampled students (n=8,651) attending public, privat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 45 publications
2
40
0
Order By: Relevance
“…The IPAQ-short was used in the present study because data were collected as part of a routine clinical screening assessment and brevity was a priority; this may have resulted in underestimation of physical activity in this group. For example, Widome et al (2011) found that Iraq/Afghanistan veteran college students engaged in more strength training and comparable rates of other weight management behaviors when compared with college students without a military background; strength training was not specifically assessed in the present study. Lastly, the strength of associations between physical activity and severity of somatic and depressive symptoms is relatively weak, suggesting that there are other unmeasured physical activity correlates and indicating a need for further research in this area.…”
Section: Limitations and Strengthsmentioning
confidence: 73%
“…The IPAQ-short was used in the present study because data were collected as part of a routine clinical screening assessment and brevity was a priority; this may have resulted in underestimation of physical activity in this group. For example, Widome et al (2011) found that Iraq/Afghanistan veteran college students engaged in more strength training and comparable rates of other weight management behaviors when compared with college students without a military background; strength training was not specifically assessed in the present study. Lastly, the strength of associations between physical activity and severity of somatic and depressive symptoms is relatively weak, suggesting that there are other unmeasured physical activity correlates and indicating a need for further research in this area.…”
Section: Limitations and Strengthsmentioning
confidence: 73%
“…The amount of time a participant spent per day watching television and using a computer for something that was not for work or school work, was used to assess screen time. 33 Categories of ≥14 hours/week vs. <14 hours/week were created for screen time in line with recommendations for young people of less than two hours per day. 34 Unhealthy weight control behaviors, which included taking diet pills, vomiting, or taking laxatives and was categorized as any vs. none.…”
Section: Methodsmentioning
confidence: 99%
“…Of the student Veterans surveyed, a significant number endorsed experiencing anxiety (35%), depression (24%), and PTSD symptoms (46%). Student Veterans have also been found to engage in increased health risk behaviors; a recent survey of 8,651 students found that student Veterans endorsed more safety-, tobacco-, and alcohol-related risk behaviors than civilian students [16]. Recent epidemiologic data support the preventative value of access to care, reporting that male Veterans under 30 who access VHA healthcare services are less likely to complete suicide than Veterans who do not utilize VHA care [17].…”
Section: Introductionmentioning
confidence: 89%